Economic Status of Older German Immigrants - Robert L. Clark; Ann York (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
The income of married couples in which the husband is an immigrant aged 50 and older is compared to that of native- born Germans for the period 1995 to 1997. Immigrants are divided into households that arrived in Germany before and after 1984. Using Samples A, B, and D of the GSOEP, the income of immigrants is shown to be significantly lower than that of the native-born German population for households aged 50 to 59 as well as those aged 60 and older. Differences in income appear to be the result of lower earnings for the younger households and lower retirement benefits for the older households.
Keywords: 330; Haushaltseinkommen; Alte Menschen; Einkommensverteilung; Deutschland; Migranten